Implementing the Place-Train Approach in Train-Place Services: Organizational Culture and Supported Employment - Støren-Vaczy, Blanka; Bakkeli, Vidar (Nordic Journal of Working Life Studies, 2024)
Supported employment (SE) is increasingly implemented in employment services worldwide. The disruptive character of SE, involving a shift from ‘train-place’ to ‘place-train’ models of vocational rehabilitation, has led to growing recognition of implementation challenges and problems that negatively influence service efficacy and employment outcomes.This article enriches existing literature by presenting a theoretical framework that conceptualizes how organizational culture within public employment services can impact SE implementation. The argument is illustrated with cases from the Norwegian Employment and Welfare Service (NAV). Organizational culture plays a crucial role in shaping employee actions, behaviors, and foundational assumptions, which in turn influence local interpretations and applications of SE. Using Yin’s (2018) ‘embedded single case study’ method, our research concentrates on various units of analysis within a singular case. Our findings underscore the importance of considering organizational culture and context, acknowledging SE’s disruptive nature, and recognizing the nonlinear dynamics of implementation processes.